Dynamics and Stability Results for Nonlinear Neutral Pantograph Equations via Hilfer-Hadamard Fractional Derivative - Vivek, D.; Kanagarajan, K.; Harikrishnan, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
A study on the existence and uniqueness of a solution for nonlinear neutral pantograph equations with Hilfer-Hadamard fractional derivative is the main aim of this paper. The existence result is obtained by using Schauder fixed point theorem. Also, we discuss Ulam stability for these equations based on Banach contraction principle.